A guide to international climate mitigation policy and finance frameworks relevant to the protection and restoration of blue carbon ecosystems - Vanderklift, M.; Herr, D.; Lovelock, C,; Murdiyarso, D.; Raw, J.; Steven, A.D. (Frontiers Media, 2022)
The protection, management and restoration of vegetated ecosystems on land and in the ocean (‘natural climate solutions’) can be a useful strategy for reducing net greenhouse gas emissions to help limit global warming. Their potential contribution to reducing net emissions has led to the development of policies and financial incentives for their protection and restoration. These have in turn created a set of expectations among some stakeholders, and interest in expanding these to encompass other ecosystems. However, there are specific rules about how abatement is calculated in international policy and climate finance, and the frameworks and terminology associated with them are often complex. This can be a barrier to stakeholders who want to leverage the potential of natural climate solutions, sometimes leading to incongruence between realised and anticipated benefits. In this article, we attempt to outline some of the key international policy and carbon market frameworks for coastal ‘blue carbon’ ecosystems, and the extent to which different ecosystems are accommodated. Currently, among the coastal ecosystems, only mangrove forests, seagrass meadows, and tidal marshes are typically considered in international policy and carbon market frameworks. The defining feature of these ecosystems is that the foundation species are plants that grow in sediment (soil). They are the only coastal ecosystems currently included in IPCC guidelines for national greenhouse gas inventories, and in compliance and voluntary carbon markets. There is interest in potentially including other marine ecosystems, such as kelp forests and unvegetated tidal flats, into carbon accounting frameworks, but there are unresolved questions about whether sequestration and storage of carbon by these ecosystems meets the rigorous standards required. Voluntary carbon markets have greater flexibility than mechanisms linked to national greenhouse gas inventories, and so might be early implementers of expanding methods to include other ecosystems. Incorporating coastal ecosystems into national greenhouse gas inventory is a useful action countries can take that will likely help generate incentives for protection and restoration of these important ecosystems.